Soil quality index and patchouli yields on various cropping systems in Aceh province, Indonesia: Case study in Aceh Barat Regency - Khairun Nisa; Sufardi Sufardi; Muhammad Rusdi; Indra Indra (Case Studies in Chemical and Environmental Engineering)
Patchouli (Pogostemon cablin Benth.) cultivation in Aceh Barat Regency faces challenges in optimizing yield and soil quality. This study aimed to evaluate the effects of monoculture, intercropping, and mixed garden systems on soil quality and patchouli yields. Using the Mausbach and Seybold method to determine the Soil Quality Index (SQI), the study found the mixed garden system had the highest SQI, biomass, and patchouli alcohol (PA) content, although none meet the Indonesian national standards (SNI) (21.47 ± 0.65 % to 27.68 ± 0.90 %). The findings emphasize the need for optimal cropping systems to enhance sustainable patchouli production.